THE EFFECT OF ADDITION OF FIBER REINFORCED ON CONCRETE WITH PLAIN AND DEFORM REBAR - Kurdian Suprapto (Journal of Civil Engineering, 2010)
In reinforced concrete structures, the interaction between concrete and steel bar are depend on its bonding strength. This study presents the behavior of bond-slip on fiber reinforced concrete with 10 mm plain rebar and deforms rebar. The concrete specimen is using 1% fiber reinforced. Furthermore the specimen is also compared with concrete without fiber reinforcement. The behavior that observed in this study is the effect concrete compressive strength, type of rebar, amount of rebar, and concrete cover due to bonding strength. The analysis results also compared between pull out method and semi beam method with and without fiber reinforcement. The analysis results shows the compressive strength, tensile strength, bonding strength, and bond stress of fiber reinforced concrete increase around 13.255%, 48.70%, 10.43% and 10.53%, respectively. Moreover, the deform rebar has better bonding strength compared to the plain rebar, which increase around 175% - 185%. Furthermore, for the group reinforcement, which is the spacing between rebar is 2.5 cm, is also effected the bond stress. The more amount of rebar will reduce the bond stress around 46.82% - 64.71%. In addition, the more thickness of concrete cover will also increase the bond stress.